1990
DOI: 10.1111/j.1365-2621.1990.tb05198.x
|View full text |Cite
|
Sign up to set email alerts
|

Headspace Volatiles and Sensory Characteristics of Ground Beef from Forage‐ and Grain‐Fed Heifers

Abstract: Twenty-seven yearling Hereford-Angus heifers were allotted to one of three intense managed pasture systems: Tifleaf pearl millet, sorghum sudangrass and fescue-clover. After grazing, heifers were finished in drylocand then serially slaughtered a;O, 52:&d 82 days in the feedlot (DIF). A total of 51 volatilcs were identified in ground beef from &Gssimus dorsi (L. dorsi) muscle and subcutaneousfat. Major classes of volatile compounds identified included hydrocarbons and aldehydes plus fewer numbers of ketones, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 29 publications
4
38
1
Order By: Relevance
“…The panel in Britain preferred grass‐fed lamb, whereas the Spanish panel preferred concentrate‐fed lamb, reporting distaste for the “grassy” flavor. A similar tendency was observed by Larick and Turner (1990) for US sensory panels, who also preferred concentrate‐fed beef over pasture‐fed beef. Collectively, these results demonstrate that familiarity is a driving force behind consumers’ decision making.…”
Section: Effects Of Farming Systems On Meat Qualitysupporting
confidence: 82%
“…The panel in Britain preferred grass‐fed lamb, whereas the Spanish panel preferred concentrate‐fed lamb, reporting distaste for the “grassy” flavor. A similar tendency was observed by Larick and Turner (1990) for US sensory panels, who also preferred concentrate‐fed beef over pasture‐fed beef. Collectively, these results demonstrate that familiarity is a driving force behind consumers’ decision making.…”
Section: Effects Of Farming Systems On Meat Qualitysupporting
confidence: 82%
“…In a US study, Larick et al (1987) observed that steers finished on red clover (Trifolum pratense) had a higher "grassy" flavour than those fed grass (Festuca arundinacea), and grass-fed animals produced meat that was not only higher in PUFA but which was also oxidatively more unstable (Larick and Turner, 1990a). They attributed these differences in flavour to both the increased content of PUFA, particularly α-linolenic acid in the phospholipid fraction, its lower oxidative stability, and to odoriferous compounds stored in the depot fats (Larick and Turner, 1990b). In European studies it has been confirmed that feeding fresh, green forages not only promotes the content of PUFA in meat, but also contributes antioxidants such as α-tocopherol and β-carotene to the meat, which stabilise the fatty acids and improves the meat quality (Richardson et al, 2004;Gatellier et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…Although PUFA do not constitute a large component of the total fatty acid percentage, it has been reported that PUFA may be responsible for off-flavors in red meats due to the lipid oxidation process (Vatansever et al, 2000). Some of the compounds that result from PUFA oxidation include aldehydes, alcohols and ketones (Larick et al, 1987;Larick and Turner, 1990a;Elmore et al, 1999). As well, Wood et al (2003) concluded that if C18:3 cis-9,12,15 levels account for approximately 3% of the lipid fraction it may be detrimental to desirable flavor production.…”
Section: Relationship Of Fatty Acids and Sensory Off-flavormentioning
confidence: 99%